Economic Geology Models 1. Geochemical Exploration and Metallogenic Studies, Northern Chile - Cameron, Eion; Leybourne, Matthew; Palacios, Carlos; Reich, Martin (Geoscience Canada, 2008)
SUMMARY Research was initiated in 1998 on geo-chemical methods of exploration for copper porphyry deposits buried under thick, lithified piedmont gravel cover in the Atacama Desert, Chile. Early data suggest that mineralized, saline groundwater has been episodically forced up through fracture zones to the surface during earthquakes, creating geochemical anomalies above ore deposits. Follow-up research supported by the Canadian Mining Industry Research Organization (CAMIRO) examined the composition of both groundwater and surface anomalies, confirming a link between the two. Further work suggests that the geo-chemical anomalies are the surface expression of a process common to the metallogenic evolution of many deposits. Porphyry intrusion and hypo-gene mineralization are controlled by faults, and are followed by supergene enrichment in a semi-arid climate. After burial by Miocene gravels, the climate changed to hyper-arid; estimates of the onset of hyperaridity vary from mid-Miocene (11–14 Ma) to Pliocene (~3–5 Ma). Since then, saline dewatering of the basement along long-lived faults has converted the original super-gene copper oxide assemblage, formed in equilibrium with meteoric water and lacking atacamite, to one containing atacamite [Cu2Cl(OH)3], the copper mineral especially associated with northern Chile. This interpretation is supported by studies showing that the salinity of fluid inclusions in atacamite is similar to that of local groundwater and that atacamite is considerably younger than the co-existing supergene alteration.